Employer Brand Opens up for a Gender Process Model - Lundkvist, Hans (Nordic Journal of Working Life Studies, 2011)
Regardless of a long tradition of legislation, policymaking and practical achievements, the issues ofgender equality and of the segregated labor market still remain a matter of concern in Sweden. Thispaper describes a collaborative process between a research project and an engineering enterprise.It describes the point of departure, based on the concept of employer brand, of a long-term changeprocess and the different phases and activities during an intensive period 2009. The collaborationaimed to develop innovative methods, and to apply them in order to achieve increased genderawareness, and thereby to be able to retain and attract the best labor for tomorrow. Differentapproaches and methods as analogies, anecdotes, and pictures were used to nourish the process.Findings showed that the interactive process contributed to increased awareness. During the processthe enterprise became more conscious of the potential of being a gender equal employer